Prevalence and Abundance of Cyamid “Whale Lice” (Cyamus ceti) on Subsistence Harvested Bowhead Whales (Balaena mysticetus) - Von Duyke, Andrew L.; Stimmelmayr, Raphaela; Sheffield, Gay; Sformo, Todd; Givens, Geof H.; George, John C. (ARCTIC, 2016)
We present findings on the prevalence and abundance of cyamid ectoparasites (Cyamus ceti) or “whale lice” on bowhead whales (Balaena mysticetus) harvested for subsistence in the Bering, Chukchi, and Beaufort Seas from 1973 to 2015. Cyamids were present on 20% of the 673 whales that were examined for cyamid ectoparasites. Logistic regression was used to determine factors associated with cyamid prevalence. The probability of cyamid presence increased with age, length, and improving body condition, but decreased over the past 35 years. Cyamid presence was also more probable on whales harvested in the spring than on those harvested in the fall. When present, cyamid abundance was typically low(< 10 per whale). Case histories provide ancillary information about the relationships between abundance of cyamids and their bowhead hosts. Environmental change and increasing anthropogenic disturbances are expected to occur in the Arctic regions inhabited by bowheads. We recommend continued monitoring of subsistence harvested whales for cyamids, as well as further investigations into the roles of environmental and anthropogenic variables in cyamid prevalence and abundance, as part of a comprehensive program of Arctic ecosystem assessment. Nous présentons nos constatations en matière de prévalence et d’abondance de l’ectoparasite cyamidae (Cyamus ceti) ou « pou des baleines » se trouvant sur la baleine boréale (Balaena mysticetus) capturée à des fins de subsistance dans la mer de Béring, la mer des Tchouktches et la mer de Beaufort entre 1973 et 2015. Les cyamidae étaient présents sur 20 % des 673 baleines qui ont été examinées dans le but d’y trouver des ectoparasites cyamidae. La régression logistique a servi à déterminer les facteurs liés à la prévalence de cyamidae. La probabilité de la présence de cyamidae augmentait en fonction de l’âge, de la longueur et de l’amélioration de l’état corporel, mais elle a diminué au cours des 35 dernières années. De plus, la présence de cyamidae était également plus probable chez les ...